Konsep Ta’zir dalam Pandangan Psikologi Pendidikan Islam di Pondok Pesantren Al-Falah Kabupaten Pesisir Barat - zaini firdaus; Siti Roudhotul Jannah (STAI Darussalam Lampung, 2022)
Abstract Al-Falah Krui Islamic Boarding School, West Coast is one small example that is the focus of this article. The cottage is also known as Islamic Boarding School which has a complete education. Starting from formal institutions such as Madrasah Ibtidaiyah (MI), Madrasah Tsnawiyah (MTs), and Madrasah Aliyah (MA). Informal Madrasah Diniyah Institutions, Tahfidz Al-Qur'an, Islamic Boarding Schools. Of course, with the complexity of education in the Islamic Boarding School, rules and punishments (Ta'zir) are needed as an effort to control and discipline students. Thus, in the focus of this research, the author will study further with a psychological approach entitled Tazir Concept in the Psychology of Islamic Education at Al-Falah Islamic Boarding School, Pesisir Barat Regency. The approach used in this research is a descriptive qualitative research approach. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from research subjects and observable behavior